2018
DOI: 10.1038/pr.2017.329
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D ameliorates neonatal necrotizing enterocolitis via suppressing TLR4 in a murine model

Abstract: BACKGROUND: The toll-like receptor 4 (TLR4) has been reported to play an important role in necrotizing enterocolitis (NEC). As an established regulator of TLR4, vitamin D has been demonstrated to be intestinal-protective. This study aims at finding out whether the vitamin D/vitamin D receptor (VDR) pathway ameliorates NEC by regulating TLR4. METHODS: Serum 25-hydrovitamin D (25(OH)D) was tested and compared in 15 preterm infants with NEC, 12 preterm infants without known complications and 20 healthy term infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Previous studies in animal NEC models have shown changes in expression levels of claudin-3, occludin and ZO-1 (Clark et al, 2006;Khailova et al, 2009;Rentea et al, 2012;Shiou et al, 2011). Consistent with previous animal NEC studies (Clark et al, 2006;Rentea et al, 2012;Shi et al, 2018), we found a decrease in ZO-1 expression with an increase in claudin-3. Reduced expression of ZO-1 was evident in all groups, including DHK, where the mice did not show histological evidence of intestinal injury, suggesting that lower expression could be a predisposing factor and could partly explain changes in intestinal permeability in our intestinal injury model.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies in animal NEC models have shown changes in expression levels of claudin-3, occludin and ZO-1 (Clark et al, 2006;Khailova et al, 2009;Rentea et al, 2012;Shiou et al, 2011). Consistent with previous animal NEC studies (Clark et al, 2006;Rentea et al, 2012;Shi et al, 2018), we found a decrease in ZO-1 expression with an increase in claudin-3. Reduced expression of ZO-1 was evident in all groups, including DHK, where the mice did not show histological evidence of intestinal injury, suggesting that lower expression could be a predisposing factor and could partly explain changes in intestinal permeability in our intestinal injury model.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Vitamin D vitiates NF-Κb signaling, resulting in reduced epithelial cell death 83 . In the same way, a low level of maternal/neonatal 1,25-dihydroxyvitamin D was shown to be a risk for NEC development 85,86 . In accordance with the protective role of vitamin D in the context of adult IBD, Shi et al have found that vitamin D treatment significantly attenuates NEC severity in a rat model.…”
Section: Vitamin Dmentioning
confidence: 83%
“…In accordance with the protective role of vitamin D in the context of adult IBD, Shi et al have found that vitamin D treatment significantly attenuates NEC severity in a rat model. Notably, they also and found that Vitamin D significantly repressed TLR4 expression, while promoting the expression of tight junction proteins and dampening epithelial cell apoptosis 86 .…”
Section: Vitamin Dmentioning
confidence: 92%
“… 56 Although TLR4 has a signature role in host defense through its expression on immune cells, we and others have shown that TLR4 also is expressed on the intestinal epithelium, where it regulates intestinal epithelial apoptosis and migration, and proliferation, and thus contributes to the pathogenesis of NEC. 19 , 22 , 25 , 57 , 58 , 59 , 60 , 61 , 62 , 63 Evidence for a role for TLR4 in human NEC from a variety of investigators includes the observations that levels of expression of TLR4 messenger RNA and protein are both significantly higher in the intestine of patients with NEC as compared with control patients, while activating mutations in the TLR4 signaling pathway are found in a greater proportion of premature infants with NEC as compared with those without this disease. These findings suggest but by no means prove the fact that TLR4 activation plays a role in NEC development.…”
Section: Toll-like Receptor Activation Leads To Nec Development By Inmentioning
confidence: 99%